Breast and Formula Milk and Early Puberty Onset - Valeria Calcaterra; Hellas Cena; Francesca Sottotetti; Virginia Rossi; Federica Loperfido; Gianvincenzo Zuccotti (MDPI AG, 2023)
Nutrients have an enormous impact on many hormonal systems and aspects of health, and nutrition status is a crucial regulator of growth and pubertal development in children and adolescents. In this narrative review, we explore the connection between these feeding methods and the timing of puberty to provide a clearer understanding of how infant nutrition might contribute to the early development of puberty. Puberty is a key stage in the transition from childhood to adulthood and the timing of puberty represents a significant biological milestone of growth. Breast milk seems to have a pivotal role in puberty onset, mainly due to its dynamism, which shape indirectly the gut microbiota in early life, besides direct exposure of the baby to the milk microbiota through gut-breast axis. Concerning breast and formula milk and their effects on the onset of puberty, a protective role of the former occurs. As for the potential harmful effects of soy-based formulas and the isoflavones that they contain, the studies reported demonstrate conflicting opinions, underlining the need for further research on this topic. A healthy and well-nourished diet from the earliest stages of life has significant preventive potential for overall well-being, reducing the risk of many health problems later in life.